PERWATAKAN TOKOH UTAMA PRIA PADA KUMPULAN CERPEN ALUMNI UNESA â€œNDORO, SAYA INGIN BICARAâ€: DALAM PERSPEKTIF PENGARANG WANITA - Kocimaheni, Amira Agustin (Paramasastra: Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2018)
UNESA alumni compilation of short stories with the title â€œNdoro Saya Ingin Bicaraâ€ consists of short stories written by some women. With the existing view that men supremacy has always been stronger (the authority), even in the literary works, leads to the interest of finding out how women writers describe the male main character in their short stories. Especially, those women writers are also career women in their fields.